The Gut Microbiota Profile According to Glycemic Control in Type 1 Diabetes Patients Treated with Personal Insulin Pumps - Sandra Mrozinska; Przemysław Kapusta; Tomasz Gosiewski; Agnieszka Sroka-Oleksiak; Agnieszka H. Ludwig-Słomczyńska; Bartłomiej Matejko; Beata Kiec-Wilk; Malgorzata Bulanda; Maciej T. Malecki; Pawel P. Wolkow; Tomasz Klupa (Microorganisms, 2021)
Recently, several studies explored associations between type 1 diabetes (T1DM) and microbiota. The aim of our study was to assess the colonic microbiota structure according to the metabolic control in T1DM patients treated with insulin pumps. We studied 89 T1DM patients (50.6% women) at the median age of 25 (IQR, 22–29) years. Pielou’s evenness (p = 0.02), and Shannon’s (p = 0.04) and Simpson’s diversity indexes (p = 0.01), were higher in patients with glycosylated hemoglobin (HbA1c) ≥ 53 mmol/mol (7%). There were no differences in beta diversity between groups. A linear discriminant analysis effect size (LEfSe) algorithm showed that one family (Ruminococcaceae) was enriched in patients with HbA1c < 53 mmol/mol, whereas one family (Streptococcaceae) and four species (Ruminococcus torques, unclassified species of Lactococcus, Eubacteroim dolichum, and Coprobacillus cateniformis) were enriched in patients with HbA1c ≥ 53 mmol/mol. We found that at class level, the following pathways according to Kyoto Encyclopedia of Genes and Genomes were enriched in patients with HbA1c < 53 mmol/mol: bacterial motility proteins, secretion system, bacterial secretion system, ribosome biogenesis, translation proteins, and lipid biosynthesis, whereas in patients with HbA1c ≥ 53 mmol/mol, the galactose metabolism, oxidative phosphorylation, phosphotransferase system, fructose, and mannose metabolism were enriched. Observed differences in alpha diversity, metabolic pathways, and associations between bacteria and HbA1c in colonic flora need further investigation.